The effect of cooperative game teams' strategy of cooperative learning on learning some basic tennis skills for students - Muhammad Hussein Muhammad, Qusay; Mohammed Abbood, Ruaa (International Journal of Psychosocial Rehabilitation, 2020)
Physical education and sports science is one of the educational institutions that provide the learner with the scientific and mathematical aspects in order to be healthy in the body and able to lead sports institutions and provide clubs with athletes of nullification according to the sciences that are provided to the learner during his studies. Kinetic learning is one of those important and fundamental sciences because it is the basis for learning any mathematical game and building it rightThe importance of the research comes to clarify the role and importance of the teaching method according to the strategy of tasks, the cooperative games teams in the cooperative method to upgrade the basic skills of tennis, and thus we reduce the time and effort of the learner and the teacher.